Multiplying factors of Tunjuelo River (2018)
(Eng) The most important sources of pollution in urban rivers are the sewage system discharges, disturbing the quality and behavior patterns of water resources. The Tunjuelo River is one of the most polluted and important stream from Bogota city, receiving numerous wastewater discharges. Therefore, its sanitation has become one of the main objectives of the environmental authority. However, in order to take action is necessary to understand the water quality behavior specifically loads patterns. This article shows the results of the load multiplier factors for total suspended solids (TSS) and biochemical oxygen demand (BOD), these factors were calculated to understand the behavior of wastewater discharges and at different points on the river. Finally, each discharge has its own characteristics that affect differently the behavior of the river downstream, resulting in a distortion in the flow pattern in most of the sampled points.